Voices of the childhood: reflecting educational practices of research and the contributions of the concept of Symbolic Violence - Roberto Sanches Mubarac (Universidade Federal de Santa Catarina, 2007)
The research work with children is in the area of the education or in the several areas of the social sciences, it involves dimensions and cares, extremely important that should orientate the planning process, execution and evaluation of the action of the pesquisador/investigador. In this text, I will try to discuss in an introductory way such concerns focalizing, however, as key category of the reflections here proposed, the concept of Symbolic Violence in Pierre Bourdieu and the contributions that the author can still bring to that research process full of gaps and subjects that dispute of the social sciences a search effort.